Assessing the Resilience of the Marine Economy: A Case Study of Southern China’s Marine Economy Circle - Hu, Yue; Zhou, Han Qian; Jin, Xiao Mei; Shen, Ya Fang; Yan, Yong Zhe (Frontiers in Marine Science, 2022)
As an important part of the national economy, the marine economy will be subject to various internal and external disturbances in the process of development. Different regions will show different resilience. Based on four dimensions of “resistance–recovery–reorientation–renewal,” this paper measures the marine economic resilience of the four provinces covered within the China’s Southern Marine Economy Circle from 2008 to 2018 by establishing an evaluation index system. The results show that 1) the overall resilience of economy in the Southern Marine Economy Circle showed a fluctuating upward trend from 2008 to 2018. Although there was a decline in 2011–2012 due to natural disasters, the value quickly resumed its increasing trend. 2) At present, there are obvious relative differences in the resilience of marine economy in each region of China’s Southern Marine Economy Circle, and the polarization phenomenon is serious. Among them, Guangdong belongs to the high-value region and Fujian is in the middle, while Hainan and Guangxi are temporarily in the low-value area.